Single mission workload and influencing factors in German prehospital emergency medicine - A nationwide prospective survey of 1361emergency missions - Prottengeier, Johannes; Keunecke, Johann Georg; Gall, Christine; Eiche, Christian; Moritz, Andreas; Birkholz, Torsten (Scandinavian Journal of Trauma Resuscitation & Emergency Medicine, 2019)
Background: Workload is a major determinant of system performance and human well-being. This study aims to evaluate workload in prehospital emergency medicine on a single mission level and investigates influencing factors originating from medical scenarios, patient-provider interaction, EMS logistics and teamwork. Methods: In a nationwide study, German paramedics were asked to evaluate single missions for perceived workload by completing the NASA Task-Load-Index (TLX). A variety of candidate variables were documented and tested for influence on the TLX through multivariate regression analysis. Results: One thousand three hundred sixty-one emergency missions were analysed. Global workload scored in medium ranges (Median TLX 41.00/100; IQR 24.25-57.50). 263 missions achieved very low (< 20/100) and 52 missions achieved very high (> 80/100) levels of workload. Severity of distress as indicated by the NACA score (delta TLX 2.71 per 1 NACA point), execution of invasive procedures (e.g. delta TLX 8.20 for intravenous access), obese patients (delta TLX 0.05 per 1 kg of weight) and aggression incidences (e.g. delta TLX 10.54 for physical aggression), amongst others, resulted in significant increases in workload. Good teamwork decreased workload by 2.18 points per 1 point on the Weller-Teamwork Measurement Tool. Conclusion: Distinct factors result in significant increases in workload for EMS paramedics. Improvements in training for certain medical scenarios, strategies against aggression events and enhancements in EMS logistics - especially for the transfer of obese patients - should be implemented and tested for their presumably positive effect on workload, EMS performance and paramedics' well-being.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Emergency medical service; Ergonomics; Human factors; NASA task-load-index; Paramedic; Teamwork; Workload